Lithium slag iron removal process, product and application

By combining magnetic separation and high-temperature and high-pressure acid leaching, the iron impurities in the lithium slag were successfully removed, solving the problem that the lithium slag could not meet the requirements of ceramic materials, and achieving efficient and economical iron removal effect of lithium slag.

CN119771881APending Publication Date: 2025-04-08NINGBO INST OF TECH ZHEJIANG UNIV ZHEJIANG

Patent Information

Application Number
CN202510042994.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove iron impurities in lithium slag, especially weak magnetic iron impurities, such as Federov silicate, which causes lithium slag to fail to meet the raw material requirements of ceramic materials.

Method used

A process combining physical and chemical methods, including magnetic separation and hydrochloric acid reaction under high temperature and high pressure conditions, is used to remove harsh magnetic and weak magnetic iron impurities in lithium slag through strong magnetic separation and weak magnetic separation.

Benefits of technology

It realizes efficient removal of iron impurities in lithium slag, reduces the iron content to less than 0.5%, and at the same time improves the whiteness of lithium slag, meets the requirements of ceramic materials, and reduces the use of chemical reagents and the treatment cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237504450000051
    Figure BDA0005237504450000051
  • Figure BDA0005237504450000061
    Figure BDA0005237504450000061
  • Figure BDA0005237504450000062
    Figure BDA0005237504450000062
Patent Text Reader

Abstract

The invention relates to the technical field of resource recycling, in particular to a lithium slag iron removal process, a product and application. The method comprises the following steps: S1, magnetic separation: sequentially carrying out strong magnetic separation and weak magnetic separation on the lithium slag; s2, acid leaching treatment: adding the lithium slag subjected to magnetic separation treatment into an acid solution, and reacting under high-temperature and high-pressure conditions to obtain slurry; and S3, carrying out solid-liquid separation on the slurry subjected to acid leaching treatment, collecting solids, washing and drying to obtain a lithium slag product subjected to iron removal. The invention provides a lithium slag iron removal process combining a physical method and a chemical method, iron impurities in the lithium slag can be effectively removed, particularly weak magnetic iron impurities (such as Feidelov silicate Fe2HK4O21Si8) in the lithium slag can be removed, the whiteness of a final product is relatively high, and a new technical thought is provided for high-value utilization (such as preparation of ceramic materials) of the lithium slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of resource recycling, and in particular to a lithium slag iron removal process, a product and an application thereof. Background Art

[0002] Lithium slag refers to a type of by-product produced in the production process of lithium products, and its main components are silicon dioxide, aluminum oxide and iron oxide. Lithium slag has high hardness, toughness and stability, and is also resistant to high temperatures and chemically inert. Since lithium slag is a solid waste generated in the lithium production process, the industry mainly disposes of lithium slag by building storage yards or landfills. In order to improve the utilization rate of resources, the industry is also exploring the reuse of lithium slag to achieve its high added value. However, there are still some problems in practical applications. For example, when lithium slag is used to make ceramic materials, the iron oxide component in the lithium slag will affect the color of the ceramic materials. Therefore, separating iron impurities in lithium slag is one of the key issues in realizing the reuse of lithium slag.

[0003] There are many forms of iron impurities in lithium slag, including strong magnetic iron impurities and weak magnetic iron impurities. Strong magnetic substances in lithium slag can usually be removed by magnetic separation, while weak magnetic substances need to be removed by different chemical reaction methods considering their chemical properties. For example, there is a weak magnetic substance in lithium slag, Fe2HK4O 21 Si8), as a complex silicate mineral containing iron, potassium, silicon and oxygen, has a certain chemical inertness under normal conditions and is difficult to remove by acid leaching at a relatively low temperature (e.g., less than 100°C) and normal pressure. Therefore, the iron impurities in lithium slag still maintain a relatively high content. At present, the methods for removing iron from lithium slag mainly include single technologies such as physical separation (such as magnetic separation) and chemical reaction (acid leaching), but there are often problems such as low processing efficiency, high residual iron impurities or high processing costs.

[0004] Chinese patent CN117165787B discloses a method for extracting lithium from spodumene while recovering low-iron and low-sulfur silicon-aluminum powder, high-purity gypsum, tantalum-niobium concentrate and lithium-rich iron material. Through the process steps of grinding-magnetic separation-gravity separation, tantalum-niobium minerals are effectively enriched, and tantalum-niobium ore is efficiently separated from lithium slag. Through acid washing, tantalum-niobium ore is refined. However, the iron content in the final product of this technology is still relatively high (more than 1%), which cannot meet the raw material requirements of ceramic materials.

[0005] Chinese patent application CN116119692A discloses a process for extracting lithium carbonate by reconstructing the lepidolite phase. The technology is based on the lithium carbonate of lepidolite ore for phase reconstruction, and then extracting lithium and recycling lithium slag, which improves the conversion rate of lithium, performs secondary leaching of raw materials, and effectively improves the leaching efficiency of lithium sulfate. However, the technology does not effectively remove iron impurities in lithium slag, and the method uses a large amount of chemical reagents, and the processing steps are cumbersome and costly.

[0006] In this context, the development of an efficient and economical lithium slag iron removal technology is of great significance for the high-value utilization of lithium slag. Summary of the invention

[0007] In order to solve the above technical problems, the present invention proposes a lithium slag iron removal process combining physical and chemical methods, which can effectively remove iron impurities in lithium slag, especially weakly magnetic iron impurities (such as Fedorov silicate Fe2HK4O 21 Si8), and the final product has a high whiteness, which provides a new technical idea for the high-value utilization of lithium slag.

[0008] The first aspect of the present invention provides a lithium slag iron removal process, the steps comprising:

[0009] S1. Magnetic separation: The lithium slag is placed in a magnetic separator and sequentially subjected to strong magnetic separation and weak magnetic separation;

[0010] S2. Acid leaching treatment: adding the lithium slag after magnetic separation treatment to an acid solution, reacting under high temperature and high pressure conditions to obtain a slurry;

[0011] S3. The slurry after acid leaching is subjected to solid-liquid separation, the solid is collected, washed and dried, and a lithium slag product after iron removal is obtained.

[0012] There are inevitably some weakly magnetic iron substances in lithium slag, such as Fedorov silicate (Fe2HK4O 21Si8), etc. The presence of these impurities makes lithium slag unable to meet the preparation of ceramic raw materials, etc., affecting the recycling of lithium slag. In order to realize the high added value utilization of lithium slag, the prior art attempts to remove iron from lithium slag by magnetic separation, but the iron impurity content of lithium slag after iron removal (converted to Fe2O3) is still higher than 0.8%, which cannot meet the requirements of iron content below 0.5% required by ceramic raw materials. The prior art also attempts to use acid solution to remove iron from lithium slag. Although the acid solution can remove iron impurities to a certain extent, Federov silicate has good chemical stability and shows strong tolerance to acid. It is not easy to react with water or acid at normal temperature and pressure. That is: single magnetic separation equipment removal and conventional acid leaching treatment cannot effectively remove iron impurities in lithium slag. Although the technical means of heating and increasing acid concentration can remove iron impurities, there are problems of high energy consumption, high risk factor, large consumption of chemical reagents and high processing cost. After a large number of experimental investigations, the present invention found that the method of combining physics (magnetic separation) with chemistry (hydrochloric acid reaction under high temperature and high pressure conditions) can not only achieve efficient iron removal, but also reduce the use of chemical agents. At the same time, the whole process meets environmental protection and safety requirements, and has positive technical guiding significance.

[0013] In some preferred embodiments, the strong magnetic separation is carried out in a first magnetic field, and the magnetic field strength of the first magnetic field is 1-2T, which can be listed as 1T, 1.1T, 1.2T, 1.3T, 1.4T, 1.5T, 1.6T, 1.7T, 1.8T, 1.9T, and 2T.

[0014] More preferably, the magnetic field strength of the first magnetic field is 1-1.8T, most preferably 1.4T.

[0015] In some preferred embodiments, the weak magnetic separation is performed in a second magnetic field, and the magnetic field strength of the second magnetic field is 0.3-0.5T, which can be 0.3T, 0.4T, or 0.5T.

[0016] More preferably, the magnetic field strength of the second magnetic field is 0.4T.

[0017] The present invention sets a strong magnetic field interval and a weak magnetic field interval to effectively separate impurities with different magnetic properties. The strong magnetic field interval (1-2T) is preferably used to remove most of the strong magnetic substances (such as magnetite, iron oxides, etc.) in the lithium slag, and then the weak magnetic field interval (0.3-0.5T) is used to remove some weak magnetic substances. Through the above magnetic separation steps, strong magnetic impurities can be efficiently separated, and the content of iron impurities can be reduced to a certain extent, which is beneficial to the removal of iron by chemical reaction. However

[0018] In some preferred embodiments, the S1 step comprises:

[0019] The lithium slag is mixed with water to prepare slurry, and the slurry is placed in a first magnetic field for strong magnetic separation for 5-20 minutes; then the slurry is placed in a second magnetic field for weak magnetic separation for 10-60 minutes.

[0020] In some preferred embodiments, the solid-liquid ratio of lithium slag to water in step S1 is (2-10):1 g / mL, which can be listed as 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1; more preferably 5:1.

[0021] The magnetic separator of the present invention can be selected as a periodic high-gradient magnetic separation device.

[0022] In some preferred embodiments, the reaction conditions of step S2 are: reaction temperature 100-240° C., reaction pressure 1-20 atm, and reaction time 40-200 min.

[0023] In some preferred embodiments, the solid-to-liquid ratio of the lithium slag after magnetic separation treatment and the acid solution is (2-10): 1 g / mL, which can be listed as 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1; more preferably 5:1.

[0024] In some preferred embodiments, the acid solution comprises an aqueous solution of a combination of one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, hydrofluoric acid, and citric acid; preferably, an aqueous solution of hydrochloric acid.

[0025] In some preferred embodiments, the mass concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 3-20%, which can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, and more preferably 10%.

[0026] The present invention selects a hydrochloric acid aqueous solution with a mass concentration of 3-20% to react with the lithium slag, and the dilute hydrochloric acid reacts with the iron-containing weak magnetic material (such as Fedorov silicate Fe2HK4O 21 Si8, etc.) to produce soluble iron salts (such as FeCl3 or FeCl2), thereby effectively removing the residual iron impurities in the lithium slag, solving the problem that conventional acids are difficult to remove weakly magnetic iron impurities in lithium slag, and significantly reducing the iron impurity content in the lithium slag product.

[0027] In some preferred embodiments, the S2 step comprises:

[0028] The lithium slag after magnetic separation is transferred to a high-pressure reactor, an acid solution is added according to the solid-liquid ratio, and the reaction is carried out under the conditions of 100-200° C. and 1-15 atm, and the reaction time is 60-180 min.

[0029] The separation, washing and drying conditions in step S3 are not particularly limited as long as they can achieve the experimental purpose. For example, the lithium slag is washed with clean water to remove the iron salt and acid solution remaining on the surface of the lithium slag.

[0030] In some preferred embodiments, the lithium slag is derived from waste slag produced by a lithium carbonate extraction process.

[0031] The second aspect of the present invention provides a product of the above-mentioned lithium slag iron removal process, wherein the iron content of the lithium slag product after iron removal is less than 1%, and the whiteness of the lithium slag product after iron removal is greater than 60%.

[0032] Preferably, the iron content of the lithium slag product after iron removal is less than 0.6%, and the whiteness of the lithium slag product after iron removal is greater than 60%.

[0033] More preferably, the iron content of the lithium slag product after iron removal is less than 0.5%, and the whiteness of the lithium slag product after iron removal is greater than 70%.

[0034] A third aspect of the present invention provides an application of the lithium slag iron removal process or product as described above, wherein the lithium slag product after iron removal is used to prepare ceramic materials.

[0035] Beneficial effects:

[0036] The present invention provides a lithium slag iron removal process and application thereof, which has the following advantages:

[0037] (1) The present invention preferably adopts a treatment concept combining physical (magnetic separation) and chemical (high temperature and high pressure acid leaching) processes, which can efficiently remove iron impurities in lithium slag, especially for iron impurities (such as Fedorov silicates) that are difficult to remove by acid leaching under conventional conditions.

[0038] (2) The present invention efficiently removes strong magnetic and weak magnetic iron impurities in lithium slag by setting specific strong magnetic intervals and weak magnetic intervals, and the iron content of the lithium slag product after iron removal is less than 0.5%.

[0039] (3) The present invention preferably uses a hydrochloric acid aqueous solution of a specific concentration and high temperature, high pressure and time limit, which can be effectively combined with the magnetic separation process to significantly improve the whiteness of the lithium slag while reducing the iron content of the lithium slag. The whiteness of the lithium slag product after iron removal is greater than 70%.

[0040] (4) Compared with the single acid leaching process, the present invention not only improves the quality of lithium slag products, but also can significantly reduce the use of chemical reagents, thereby reducing the processing cost of the lithium slag iron removal process.

[0041] (5) The lithium slag iron removal process of the present invention can significantly reduce the iron impurity content in the lithium slag, giving the product a higher utilization value. The obtained lithium slag product can meet the application of high value-added materials (such as ceramic materials) and has strong practicality.

[0042] (6) The overall treatment process of the lithium slag iron removal process of the present invention is safe and environmentally friendly, with relatively low energy consumption. It can reduce the negative impact on the environment while producing high-quality lithium slag, and meet the needs of mass production.

[0043] (7) The lithium slag iron removal process of the present invention has a wide range of applications. The method is not only applicable to lithium slag, but can also be extended to the treatment of other minerals or wastes containing iron impurities, providing a new technical path for resource recycling and having broad application prospects. DETAILED DESCRIPTION

[0044] Note: The unit of solid-liquid ratio in the present invention is g / mL.

[0045] Unless otherwise specified, the solvents of the solutions involved in the present invention are all water; the concentrations involved are all mass concentrations; and the raw materials used are all commercially available.

[0046] Example

[0047] Preparation Example 1-9

[0048] In Preparation Examples 1-9, lithium slag (waste slag from lithium carbonate extraction process) and water are mixed according to a solid-liquid ratio to prepare slurry, the slurry is placed in a first magnetic field for strong magnetic separation, and then the slurry is placed in a second magnetic field for weak magnetic separation, and then the iron content of the product is determined.

[0049] The experimental conditions of each preparation example and the iron content (in terms of Fe2O3) in the lithium slag after magnetic separation are shown in Table 1 below.

[0050] Table 1. Magnetic separation conditions and iron content in lithium slag after magnetic separation

[0051]

[0052]

[0053] Example 1

[0054] This embodiment provides a lithium slag iron removal process and product, the steps comprising:

[0055] S1. Magnetic separation: the steps are the same as those in Preparation Example 5.

[0056] S2. Acid leaching: The lithium slag after magnetic separation in Preparation Example 5 was transferred to a high-pressure reactor, and a 5% aqueous solution of hydrochloric acid was added at a solid-liquid ratio of 2:1 g / mL, and the reaction was carried out at 100 ° C and 1 atm for 180 min to obtain a slurry;

[0057] S3. The slurry after acid leaching is subjected to solid-liquid separation, the solid is collected, washed with clean water, and dried to obtain a lithium slag product after iron removal.

[0058] Embodiment 2-10

[0059] Example 2-10 provides a lithium slag iron removal process and product. The specific implementation method is the same as that of Example 1, except that the conditions for acid leaching treatment are set, as shown in Table 2 below.

[0060] Table 2. Acid leaching conditions

[0061]

[0062]

[0063] Performance Testing

[0064] 1. Iron content detection

[0065] The present invention uses ICP (inductively coupled plasma emission spectrometer) to detect the iron content of lithium slag before and after treatment, and evaluates the effect of the lithium slag iron removal process on removing iron impurities. The mass fraction of iron impurities (in terms of Fe2O3) in the untreated lithium slag is 2%. After the magnetic separation step of Preparation Example 1-9, the iron content in the lithium slag is reduced to about 1%. After further acid leaching treatment, the iron content in the lithium slag is reduced to less than 0.6%.

[0066] Note: The ICP test method directly measures the Fe element content, and the industry usually needs to convert it into the Fe2O3 mass fraction, that is, the Fe2O3 mass fraction m%(Fe2O3)=m%(Fe)×M(Fe2O3) / M(Fe), where m%(Fe2O3) and m%(Fe) are the mass fractions of Fe2O3 and Fe, respectively, and M(Fe2O3) and M(Fe) are the molar masses of Fe2O3 and Fe, respectively. The iron content in the lithium slag in Table 1 and Table 3 of the present invention is converted into the Fe2O3 content in the lithium slag through the above formula.

[0067] 2. Whiteness test

[0068] The present invention uses a whiteness meter to detect the whiteness of the lithium slag products after the process treatment of Examples 1-10, and the results are shown in Table 3.

[0069] Note: Whiteness refers to the degree of whiteness on the surface of a substance, expressed as the percentage of white content.

[0070] Table 3 Performance test results of Examples 1-10

[0071]

[0072]

[0073] As shown in Table 3, the iron impurity content of lithium slag treated by magnetic separation + acid leaching in the present invention is significantly reduced (to a minimum of less than 0.3%), and the color of the lithium slag product is increased from less than 50% initially to more than 70%. It can be seen that the impurity content and color of the lithium slag after treatment are significantly improved, the quality of the lithium slag is improved, and it can be better used for downstream applications. When the temperature of the acid leaching treatment is lower than 100 ° C, high-pressure reaction conditions cannot be formed in the system, resulting in a decrease in the efficiency of the chemical reaction, and the weak magnetic iron impurities in the lithium slag cannot be effectively removed. Finally, the lithium slag still retains a high content of iron impurities and cannot be put into use in subsequent applications. When the temperature of the acid leaching process is too high (such as more than 200 ° C), although the iron impurities in the lithium slag can be removed, the energy consumption and cost of the entire process are high, and the high pressure formed under high temperature conditions has a sudden increase in the risk of the pressure bearing capacity of the reactor, which is not conducive to implementation. Only by adopting the preferred process of the present invention can lithium slag with low iron content and high whiteness be obtained to meet downstream applications such as ceramic preparation.

Claims

1. A lithium slag iron removal process, characterized in that the steps include: S1. Magnetic separation: The lithium slag is placed in a magnetic separator and sequentially subjected to strong magnetic separation and weak magnetic separation; S2. Acid leaching treatment: adding the lithium slag after magnetic separation treatment to an acid solution, reacting under high temperature and high pressure conditions to obtain a slurry; S3. The slurry after acid leaching is subjected to solid-liquid separation, the solid is collected, washed and dried to obtain a lithium slag product after iron removal; The strong magnetic separation is performed in a first magnetic field, and the magnetic field strength of the first magnetic field is 1-2T; The weak magnetic separation is performed in a second magnetic field, and the magnetic field strength of the second magnetic field is 0.3-0.5T.

2. The lithium slag iron removal process according to claim 1, characterized in that: The S1 step includes: The lithium slag is mixed with water to prepare slurry, and the slurry is placed in a first magnetic field for strong magnetic separation for 5-20 minutes; then the slurry is placed in a second magnetic field for weak magnetic separation for 10-60 minutes.

3. The lithium slag iron removal process according to claim 2, characterized in that: The solid-to-liquid ratio of lithium slag to water in step S1 is (2-10): 1 g / mL.

4. The lithium slag iron removal process according to claim 1, characterized in that: The reaction conditions of step S2 are: reaction temperature 100-240° C., reaction pressure 1-20 atm, and reaction time 40-200 min.

5. The lithium slag iron removal process according to claim 1, characterized in that: The acid solution includes an aqueous solution of one or more combinations of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, hydrofluoric acid, and citric acid.

6. The lithium slag iron removal process according to claim 5, characterized in that: The acid solution is a hydrochloric acid aqueous solution, and the mass concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 3-20%.

7. The lithium slag iron removal process according to claim 6, characterized in that: The S2 step includes: The lithium slag after magnetic separation is transferred to a high-pressure reactor, an acid solution is added according to the solid-liquid ratio, and the reaction is carried out at 100-200° C. and 1-15 atm for 60-180 minutes.

8. The lithium slag iron removal process according to claim 7, characterized in that: The mass concentration of hydrochloric acid in the hydrochloric acid aqueous solution is 10%.

9. A product of the lithium slag iron removal process according to any one of claims 1 to 8, wherein the iron content of the lithium slag product after iron removal is less than 1%, and the whiteness of the lithium slag product after iron removal is greater than 55%; Preferably, the iron content of the lithium slag product after iron removal is less than 0.5%, and the whiteness of the lithium slag product after iron removal is greater than 70%.

10. An application of the product of the lithium slag iron removal process according to claim 9, characterized in that: The lithium slag product after iron removal is used for preparing ceramic materials.

Citation Information

Patent Citations

  • Process for extracting lithium carbonate through ore phase reconstruction of lepidolite

    CN116119692A

  • Method for extracting lithium from spodumene and simultaneously recovering low-iron and low-sulfur silicon-aluminum micropowder, high-purity gypsum, tantalum-niobium concentrate and lithium-rich iron material

    CN117165787B

  • Comprehensive treatment process of lithium slag

    CN114226413A

  • Method for extracting lithium from low-aluminum lithium-rich clay

    CN114934196A

  • Lithium slag comprehensive recycling method

    CN117065916A

Cited By

  • Method for removing iron from spodumene smelting slag

    CN120608204A